Kaidah Fikih Dalam Halal Dan Haram Menurut Syaikh Yusuf Al-Qardhawi - Wisnu Indradi (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2023)
In the teachings of Islam, the concept of halal and haram has a strategic role in regulating various lines of life for Muslims, including food, drink, social interaction, the economy, and various other activities. In this journal, we will provide a comprehensive explanation of the fiqh rules regarding halal and haram according to Shaykh Yusuf Al-Qaradawi. Rules regarding halal and haram are taken from sources of Islamic law, namely the Qur'an and Hadith. From the contents of these texts, it is then formulated in 11 principles of fiqh. As for the other side of these fiqh rules, they are as follows: First Rule, The Law of the Origin of Everything is Mubah, Second Rule, Deciding what is lawful and unlawful is the sole right of Allah, Third Rule, forbidding something lawful and making something lawful unlawful is the same as associating partners with Allah, Fourth Rule, forbidding something lawful will cause evil and danger, Fifth Rule, in halalness there is no need for what is unlawful, Sixth Rule, Everything that leads to unlawful is unlawful, Rule Seventh, deal with something that is unlawful, the law is unlawful, Eighth Rule, good intentions cannot change what is unlawful, Ninth Rule, stay away from doubt for fear of being involved in unlawful, Tenth Rule, there are no exceptions for servants in unlawful law and Eleventh Rule, in urgent situations it is permissible to do something that is forbidden. In addition to explaining the rules and their legal basis, we also include examples of each application of these rules.